The Effectiveness of Mindfulness-Based Cognitive Therapy on Family Functioning and Meaning in Life among Women with the Experience of Spousal Infidelity - Ahmadi Portesiyeh , Parastoo; Ebrahimi Alavige, Elahe; Abedi Firouzjaei , Fatemeh; Arab , Mobina; Ghanbari, Maedeh (Mental Health and Lifestyle Journal, 2024)
The present study was conducted with the aim of determining the effectiveness of mindfulness-based cognitive therapy on family functioning and meaning in life among women with the experience of spousal infidelity. The research method was a quasi-experimental design with a pretest–posttest and control group. The statistical population of the present study consisted of women with the experience of spousal infidelity who referred to counseling clinics in Tehran in 2023. Subsequently, 30 participants were selected from this population through convenience sampling and were randomly assigned into two groups: an experimental group (15 participants) and a control group (15 participants). The instruments used for data collection were the Family Functioning Questionnaire and the Meaning in Life Questionnaire. Participants in the experimental group received mindfulness-based cognitive therapy for 8 weeks, consisting of one 90-minute therapy session per week, whereas the control group did not receive any specific intervention. The findings indicated that the mean scores of family functioning and meaning in life in the posttest, compared to the pretest, were significantly improved in the experimental group. Therefore, mindfulness-based cognitive therapy has an effect on family functioning and meaning in life among women with the experience of spousal infidelity.